Bisphenol A removal from wastewater using self-organized TIO2 nanotubular array electrodes - Brugnera, Michelle Fernanda [UNESP]; Rajeshwar, Krishnan; Cardoso, Juliano C. [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
Photoelectrocatalytic oxidation of 0.1 mM of Bisphenol A (BPA) leads to 100% of degradation monitored by liquid chromatography with diode array optical detection (limit 1 mu g L-1) and 100% TOC removal. Optimum performance was obtained using TiO2 nanotubular array (NTA) electrodes, grown by anodization of Ti foil in 0.25 wt.% NH4F and a mixture of glycerol and water (ratio 90:10 vol.%) using an applied voltage of 20 V for 50 h. The effects of supporting electrolyte, pH. applied bias potential and BPA concentration were evaluated as to their effect on the BPA degradation kinetics and the best condition was found to be 0.1 M Na2SO4 at pH 6 as supporting electrolyte and applied bias potential of +1.5 V vs. Ag/AgCl under UV irradiation. Our findings indicate that TiO2 NTAs prepared by anodization are versatile and efficient photocatalysts for the degradation of endocrine disruptors. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Bisphenol A; Endocrine disrupter; Photoelectrocatalytic oxidation; TiO2 nanotubular array electrodes